ANALISIS PENILAIAN PERSEDIAAN BARANG DAGANG UNTUK MENCAPAI LABA YANG OPTIMAL PADA PD. MATERIAL DEDY JAYA - Rina Purwaningsih, Mulyadi, Hesti Widianti, Ida Farida (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2012)
The purpose of this research is to determine which inventory valuation method is be used in order to achieve the exact optimal profit on PD. Material Dedy Jaya, wether the First In First Out method or moving average.Object of this research is PD. Material Dedy Jaya. Method of data collected by observation, interview, documentation, and literature. Data collected were analyzed using quantitative analysis.From the calculation of the data collected is be knew that in 2011, using the moving average method ending inventory values obtained in PD. Material Dedy Jaya Rp. 60.451.353,98 with a gross profit of Rp. 617.223.353,98. Whereas using First In First Out method obtained value of ending inventory of RP, 61.341.500 with gross profit of Rp. 618.113.500. In 2012, used the moving average method of ending inventory values obtained for Rp. 58.406.749,61 with gross profit of Rp. 474.299.145,6. whereas First In First Ou t method of ending inventory value obtained is Rp. 59.524.750 with a gross profit Rp. 510.527.000.Result of this research showed that in order to achieve optimal profit, inventory valuation method is used by PD. Material Dedy Jaya, not good. Because by using First In First Out method the gross profit company more optimal.Kata kunci : Inventory, Moving Average Method, First In First Out Method, Optimal Profi.